2020
DOI: 10.1007/s00467-020-04843-6
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23—Klotho and hypertension: experimental and clinical mechanisms

Abstract: Hypertension (HTN) and chronic kidney disease (CKD) are increasingly recognized in pediatric patients and represent risk factors for cardiovascular morbidity and mortality later in life. In CKD, enhanced tubular sodium reabsorption is a leading cause of HTN due to augmented extracellular fluid volume expansion. The renin-angiotensin-aldosterone system (RAAS) upregulates various tubular sodium cotransporters that are also targets of the hormone fibroblast growth factor 23 (FGF23) and its co-receptor Klotho. FGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 147 publications
(231 reference statements)
0
22
0
2
Order By: Relevance
“… 4 It has been shown that FGF23 may participate in the pathogenesis of hypertension through the activation of RAAS. 5 , 6 Thus, we hypothesized that children with hypertension with higher FGF23 levels might have a better response to ACEIs. This study was designed to explore the value of plasma FGF23 in predicting the therapeutic efficacy of fosinopril in children with primary hypertension.…”
mentioning
confidence: 99%
“… 4 It has been shown that FGF23 may participate in the pathogenesis of hypertension through the activation of RAAS. 5 , 6 Thus, we hypothesized that children with hypertension with higher FGF23 levels might have a better response to ACEIs. This study was designed to explore the value of plasma FGF23 in predicting the therapeutic efficacy of fosinopril in children with primary hypertension.…”
mentioning
confidence: 99%
“…Although our study has provided novel insights into the pathogenesis of hypertension in Hyp mice, a key question in this context remains unanswered: what is driving the stimulation of RAAS in aged Hyp mice? It has been suggested that FGF23 hypersecretion may stimulate the RAAS through the suppression of vitamin D hormone production in CKD [ 27 , 28 ]. However, whether RAAS is regulated by vitamin D remains a controversial issue [ 29 ], and it is currently not known if this proposed mechanism may also be relevant for Hyp mice.…”
Section: Discussionmentioning
confidence: 99%
“…Kidneys: Cheng et al, 2010 ; Kuro-o, 2010 , 2019 , 2021 ; Maquigussa et al, 2018 ; Oishi et al, 2021 ; Prud’homme et al, 2017a , 2020 ; Saar-Kovrov et al, 2021 ; Takenaka et al, 2017 ; Xing et al, 2021 ; Zou et al, 2018 . Cardiovascular: Chen K, et al, 2021 ; Freunlich et al, 2021 ; Manrique et al, 2016 ; Myung et al, 2022 ; Martin-Nunez et al, 2022 ; Olejnik et al, 2018 , 2020 ; Tyrenkov et al, 2021 ; Wang F and Zheng, 2022 ; Yang et al, 2015 . Brain: Dias et al, 2021 ; Driscoll et al, 2021 ; Cararo-Lopes et al, 2017 ; Fung et al, 2022 ; Hanson et al, 2021 ; Kundu et al, 2022 ; Laszczyk et al, 2017 ; Mytych, 2022 ; Nietzel et al, 2021; Sanz et al, 2021 .…”
Section: Klotho and Neurodegenerative Diseasesunclassified